Growth of Brasenia schreberi requries good water quality and appropriate sediment nitrogen content - Wang, Tingfeng; Yang, Hangmei; Chen, Hongyi; Zhang, Wei; Liu, Zhenya; Li, Qifan; Sun, Mei (Frontiers in Plant Science, 2025)
BackgroundStem tissue structures are the basis of stem function and are essential for maintaining the normal physiological metabolism of aquatic plants. Water and sediment conditions are important factors affecting the functional characteristics and physiological metabolism of Brassenia schreberi. Due to pollution and other water and sediment issues caused by human activities, the natural habitat and population size of B. schreberi have dramatically decreased. Understanding the responses of the functional characteristics of B. schreberi to water and sediment conditions is the key to its scientific conservation and management.Objectives and methodsThis study selected Beihai Wetland in Tengchong, China, which boasts the largest natural habitat of B. schreberi, as the research site. To detect the response strategies of B. schreberi to water and sediment conditions, the photosynthetic parameters and stem structural characteristics of this species at 17 locations, as well as the water and sediment nutrient parameters at these locations were measured. We examined the relationships between the trait characteristics of B. schreberi and the water and sediment parameters by using correlation analysis. The aim was to explore the effects of sediment nutrients and water quality on the photosynthetic and stem structural characteristics of B. schreberi.Results and conclusionsB. schreberi with higher coverage exhibited higher stomatal conductance (Gs) and transpiration rate (Tr), but lower vascular bundle area and ventilation hole area (P<0.05), while the net photosynthetic rate (Pn) maintained content, indicating lower utilization efficiency of water and CO2. Water temperature (WT), sediment nitrogen content (ω(N)) and water dissolved oxygen (DO) were the main parameters affecting the characters of B. schreberi. The Pn, was significantly negatively correlated with ω(N), while it was positively correlated with DO and sediment phosphorus content (P<0.05). The findings indicate that B. schreberi requires good water quality to maintain a high photosynthetic rate and is prone to phosphorus limitation, but it has low requirements for sediment nitrogen content. The findings of this study provide a scientific basis for the habitat restoration and species-specific management of B. schreberi in degraded wetlands.